Strategi Government Public Relations Pusat Penerangan TNI dalam Mempertahankan Reputasi Lembaga TNI - Rifqi Muflih; Dany Dany (Jurnal Komunikasi Global, 2018)
Public Relations of Headquarters of the Indonesian Armed Forces (TNI Headquarters) must work with the Government Public Relations strategy to maintain a reputation by maintaining credibility, trustworthiness, reliability, and responsibility in delivering positive news to the internal and external public. This study aims to see how the government public relations strategy of the Indonesian National Armed Forces Information Center (Puspen TNI) maintained the reputation of the TNI institution. The method used in this study is a qualitative descriptive method by interviewing the Head of Puspen TNI, non-participant observation, and documentation. The results showed that Puspen TNI in maintaining the reputation of the TNI, first, maintained credibility by measuring the objectivity and quality of the news. Second, it proclaimed information about TNI and the contribution of the TNI to the nation-state to the public through mass media and social media. Third, it disseminated the news according to the facts. Forth, it reported the performance of the TNI to the external and internal public regarding responsibility to the state and nation professionally and proportionally by providing information delivered directly through the TNI website, Facebook, Twitter, Instagram, YouTube and TV public relations TNI Streaming produced by Puspen TNI. It also maintained good relations between external media and editor in chief and journalists of print, electronic and online media.